Pemanfaatan Bunga Telang (Clitoria Ternatea) untuk Pembuatan Cendol di Desa Sindanglaut, Lemahabang, Kabupaten Cirebon - Suharyani, Ine; Renny Amelia; Setyaningsih, Indah; Lestari, Tresna; Rizikiyan, Yayan; Falya, Yuniarti; Ayunda; Ahadi, Ghany; Fitriani, Vina Nurul; Maryanto, Naida Ajeng; Alifia, Fathia Putri; Tussadiyah, Halimah (Universitas Muhammadiyah Surakarta, 2025)
Cendol was known as a popular cold drink in Indonesia. To make cendol, synthetic color often used to get attractive color, but in other side this dye may have a serious problem for health. To address this issue, this program was done to practice the making of cendol by using natural dye such as butterfly pea flower which has blue-purple color. The use of natural dyes not only provides an attractive color but also offers health benefits as a natural antioxidant. In this program, we educate and practice the PKK members of Sindanglaut Village about the utilization of butterfly pea flower member in making cendol ice. The activity held on July-August 2024, involved 16 participants. The methods used in this program consisting of presentation, demonstration, and practice. The assesment about the improvement of their knowledge were done by pre- and post-tests. The results showed an increase in knowledge of participants about the benefits of butterfly pea flowers and the techniques for making cendol. In addition, the participants' enthusiasm for the training is very high, although some challenges, such as a decline in participants' motivation, were addressed with interventions like cheers and door prizes. This socialization is expected to motivate the PKK members to continue developing innovations in food and beverage preparation, as well as to promote the use of natural ingredients that are beneficial for health. In addition, this counseling can be an idea for utilizing materials available around the house to make food or drinks that can be sold, thereby increasing community income.